Retrospective Patient Data Analysis with Respect to Irresponsible SelfMedication in a Community Pharmacy Setting in Taiping (Malaysia) - A T, Sam; Nagesvararao, Naga Jothy; Vampanan, Nager Devi; T X X S, Sharon; D, Arumugam (Indian Journal of Pharmacy Practice)
This study was undertaken to determine the incidences of self-medication by means of patient data analysis in a defined time period, in a community pharmacy in Taiping (Malaysia). This was a data format-based retrospective study. A simple patient data analysis format was used. The details were filled in when the consumers (patients) came to purchase medications. The inclusion criteria were those who purchased medications without a prescription. The subjects intending to self-medicate were included. Age, gender, presenting complaints, medications purchased, social history. Atotal of 65 cases were obtained. The most common age group that purchased non-prescription drugs from the pharmacy counter falls in the age group 30-39. The number of smokers, non-smokers and alcoholics in the study were (31 cases; 47.69%), (23 cases; 35.38%) and (3 cases; 4.6%) respectively. The most common presenting complaints were headache (10 cases; 14.7%), fever (9 cases; 13.2%) and flu (10 cases; 14.7%). The proportion of self-medication was almost equal in both the genders, with 34 females and 31 males. The ethnicity noted amongst the cases were Malay (20 cases; 30.76%), Chinese (25 cases; 38.46%) and Indian (25 cases; 38.46%). The most frequently purchased medications were antihistamines (15 cases; 23%). All the cases of self-medication were inappropriate or irresponsible, in that the consumers were not at all aware of the risks associated with selfmedication. Most of them purchased the drug/s based on advices and suggestions from family members, friends and peers. There was no stringent protocol for intervention regarding dispensing medications to these consumers. The practice of self-medication was common and often irresponsible or inappropriate. Knowledge about the risks of selfmedication was poor. Health authorities must develop stringent protocols in regard to self-medication. Pharmacists have a pivotal role in ensuring that each patient who self-medicates is aware of the risks associated. This can only be achieved by appropriate intervention and counseling techniques
Keywords: Over-The-Counter medications; Irresponsible self-medication; Polypharmacy; Patient data analysis